Selection and identification of esterase-producing microorganisms - Loto, Flavia del Valle (2007)
One of the most efficient and successful means of finding new microbial enzymes is to screen a large number of microorganisms, because of their diversity and versatility. The capability of Bacillus strains to produce and to secrete enzymes has placed them among the most important industrial enzyme producers. Esterases, one of them, have important biotechnology applications, such as drug synthesis. The aim of the present study was to select and to characterize good esterase producing bacteria. Esterase-producing colonies were selected by their ability to hydrolyze á-naphthylacetate on LB plates. The selected strains were characterized with molecular and biochemical methods. Five of fifty isolations were selected because of their high levels of extracellular and cell-bound esterases production. On the basis of their biochemical and molecular properties the strains A14 y A55 appear to belong to B. pumilus, A60 y A62 to B. subtilis and M2 to B. cereus. The nucleotide sequences of the 16S rDNA are available in GenBank under the following accession numbers A14 EF462914, A55 638794, A60 EF513611, A62 EF513612 y M2 EF 513610. This characterization will provide tools for designing new enzymatic processes. PICTO-UNT 761, PIP 6062 and CIUNT 26/D308 supported this work